Proceedings of the Paralinguistic Information and its Integration in Spoken Dialogue Systems Workshop - López-Cózar Delgado, Ramón; Kobayashi, Tetsunori (Springer, 2011)
This volume includes proceedings articles presented at the Workshop on Paralinguistic Information and its Integration in Spoken Dialogue Systems held in Granada, Spain. The material focuses on the three broad areas of spoken dialogue systems for robotics, emotions and spoken dialogue systems, and Spoken dialogue systems for real-world applications The workshop proceedings are part of the 3rd Annual International Workshop on Spoken Dialogue Systems, which brings together researchers from all over the world working in the field of spoken dialogue systems. It provides an international forum for the presentation of research and applications, and for lively discussions among researchers as well as industrialists.